From Grieving to Peace: The Cross- -Community Response in the Aftermath of the Remembrance Day Bombing in Enniskillen - Mendes, Maria Clara de Lima (ABEI Journal, 2017)
This paper investigates the unexpected cross-community responsein the aftermath of the 1987 Remembrance Day Bombing in Enniskillen.The terror attack executed by the I.R.A. killed 11 people, all civilians andProtestants, and injured more than 60, becoming one of the deadliest attacks in the history of the “Troubles”. It argues that this sense of community that urged following the attack was not circumstantial and it had been there even before the bombing. This research used as primary source local newspapers, diplomatic reports and oral history.